Metal-free visible-light-enabled vicinal trifluoromethyl dithiolation of unactivated alkenes - Li, Xiaojuan; Zhang, Qiang; Zhang, Weigang; Ma, Jinzhu; Wang, Yi; Pan, Yi (Beilstein Journal of Organic Chemistry, 2021)
The difunctionalization of alkenes involving a trifluoromethylthio group (SCF3) for the conversion of versatile and readily available olefins into structurally more complex molecules has been successfully studied. However, the disproportionate dithiolation of alkenes is unknown. Herein, a transition-metal-free protocol is presented for the vicinal trifluoromethylthio–thiolation of unactivated alkenes via a radical process under mild conditions with a broad substrate scope and excellent tolerance.
Keywords: alkenes; difunctionalization; metal-free; photoredox; trifluoromethylthiolation

(untitled) - Yang, X.; Wu, T.; Phipps, R. J.; Toste, F. D. (Chem. Rev., 2015)

(untitled) - Wang, J.; Sánchez-Roselló, M.; Aceña, J. L.; del Pozo, C.; Sorochinsky, A. E.; Fustero, S.; Soloshonok, V. A.; Liu, H. (Chem. Rev., 2014)

(untitled) - O'Hagan, D. (Chem. Soc. Rev., 2008)

(untitled) - Müller, K.; Faeh, C.; Diederich, F. (Science, 2007)

(untitled) - Liang, T.; Neumann, C. N.; Ritter, T. (Angew. Chem., Int. Ed., 2013)

(untitled) - Manteau, B.; Pazenok, S.; Vors, J.-P.; Leroux, F. R. (J. Fluorine Chem., 2010)

(untitled) - Guo, S.; Cong, F.; Guo, R.; Wang, L.; Tang, P. (Nat. Chem., 2017)

(untitled) - Shao, X.; Hong, X.; Lu, L.; Shen, Q. (Tetrahedron, 2019)

(untitled) - Hansch, C.; Leo, A.; Taft, R. W. (Chem. Rev., 1991)

(untitled) - Hansch, C.; Leo, A.; Unger, S. H.; Kim, K. H.; Nikaitani, D.; Lien, E. J. (J. Med. Chem., 1973)

(untitled) - Xu, C.; Ma, B.; Shen, Q. (Angew. Chem., Int. Ed., 2014)

(untitled) - Glenadel, Q.; Alazet, S.; Billard, T. (J. Fluorine Chem., 2015)

(untitled) - Ferry, A.; Billard, T.; Langlois, B. R.; Bacqué, E. (Angew. Chem., Int. Ed., 2009)

(untitled) - Mukherjee, S.; Maji, B.; Tlahuext-Aca, A.; Glorius, F. (J. Am. Chem. Soc., 2016)

(untitled) - Boiko, V. N. (Beilstein J. Org. Chem., 2010)

(untitled) - Xu, X.-H.; Matsuzaki, K.; Shibata, N. (Chem. Rev., 2015)

(untitled) - Wu, H.; Xiao, Z.; Wu, J.; Guo, Y.; Xiao, J.-C.; Liu, C.; Chen, Q.-Y. (Angew. Chem., Int. Ed., 2015)

(untitled) - Chen, Y.; Li, L.; Ma, Y.; Li, Z. (J. Org. Chem., 2019)

(untitled) - Yin, G.; Mu, X.; Liu, G. (Acc. Chem. Res., 2016)

(untitled) - Wang, X.-X.; Lu, X.; He, S.-J.; Fu, Y. (Chem. Sci., 2020)

(untitled) - Tu, H.-Y.; Zhu, S.; Qing, F.-L.; Chu, L. (Synthesis, 2020)

(untitled) - Dhungana, R. K.; KC, S.; Basnet, P.; Giri, R. (Chem. Rec., 2018)

(untitled) - Ji, M.; Wu, Z.; Yu, J.; Wan, X.; Zhu, C. (Adv. Synth. Catal., 2017)

(untitled) - Xiang, H.; Yang, C. (Org. Lett., 2014)

(untitled) - Zhu, L.; Wang, G.; Guo, Q.; Xu, Z.; Zhang, D.; Wang, R. (Org. Lett., 2014)

(untitled) - Xu, C.; Shen, Q. (Org. Lett., 2015)

(untitled) - Zhu, Z.; Luo, J.; Zhao, X. (Org. Lett., 2017)

(untitled) - Luo, J.; Liu, Y.; Zhao, X. (Org. Lett., 2017)

(untitled) - Xiao, Q.; He, Q.; Li, J.; Wang, J. (Org. Lett., 2015)

(untitled) - Luo, J.; Zhu, Z.; Liu, Y.; Zhao, X. (Org. Lett., 2015)

(untitled) - Jia, Y.; Qin, H.; Wang, N.; Jiang, Z.-X.; Yang, Z. (J. Org. Chem., 2018)

(untitled) - Jiang, L.; Ding, T.; Yi, W.-b.; Zeng, X.; Zhang, W. (Org. Lett., 2018)

(untitled) - Yang, T.; Lu, L.; Shen, Q. (Chem. Commun., 2015)

(untitled) - Fang, J.; Wang, Z.-K.; Wu, S.-W.; Shen, W.-G.; Ao, G.-Z.; Liu, F. (Chem. Commun., 2017)

(untitled) - Xiao, Z.; Liu, Y.; Zheng, L.; Zhou, X.; Xie, Y.; Liu, C.; Guo, Y.; Chen, Q.-Y. (Tetrahedron, 2018)

(untitled) - Xiao, Z.; Liu, Y.; Zheng, L.; Liu, C.; Guo, Y.; Chen, Q.-Y. (J. Org. Chem., 2018)

(untitled) - Yin, F.; Wang, X.-S. (Org. Lett., 2014)

(untitled) - Dagousset, G.; Simon, C.; Anselmi, E.; Tuccio, B.; Billard, T.; Magnier, E. (Chem. – Eur. J., 2017)

(untitled) - Liu, Y.-L.; Qing, F.-L.; Xu, X.-H. (Eur. J. Org. Chem., 2020)

(untitled) - Liu, X.; Liang, Y.; Ji, J.; Luo, J.; Zhao, X. (J. Am. Chem. Soc., 2018)

(untitled) - Saravanan, P.; Anbarasan, P. (Chem. Commun., 2019)

(untitled) - Li, H.; Shan, C.; Tung, C.-H.; Xu, Z. (Chem. Sci., 2017)

(untitled) - Ouyang, Y.; Xu, X.-H.; Qing, F.-L. (Angew. Chem., Int. Ed., 2019)

(untitled) - Beletskaya, I. P.; Ananikov, V. P. (Chem. Rev., 2011)

(untitled) - Otsuka, S.; Nogi, K.; Yorimitsu, H. (Top. Curr. Chem., 2018)

(untitled) - Li, H.; Liu, S.; Huang, Y.; Xu, X.-H.; Qing, F.-L. (Chem. Commun., 2017)

(untitled) - Honeker, R.; Garza-Sanchez, R. A.; Hopkinson, M. N.; Glorius, F. (Chem. – Eur. J., 2016)

(untitled) - Xu, W.; Ma, J.; Yuan, X.-A.; Dai, J.; Xie, J.; Zhu, C. (Angew. Chem., Int. Ed., 2018)

(untitled) - Pluta, R.; Nikolaienko, P.; Rueping, M. (Angew. Chem., Int. Ed., 2014)

(untitled) - Rahman, M.; Buchspies, J.; Szostak, M. (Catalysts, 2019)

(untitled) - Luo, J.; Zhang, J. (ACS Catal., 2016)

(untitled) - Jin, Y.; Yang, H.; Fu, H. (Chem. Commun., 2016)

(untitled) - Straathof, N. J. W.; Cramer, S. E.; Hessel, V.; Noël, T. (Angew. Chem., Int. Ed., 2016)